Two Cases of Severe Autoimmune Thyrotoxicosis Following SARS-CoV-2 Infection - Khary Edwards MD; Iram Hussain MD (SAGE Publishing, 2021)
Since the start of the COVID-19 pandemic, there have been multiple reports of related thyroid dysfunction, most commonly, thyroiditis. The exact mechanism for this has not been elucidated, but it is known that thyroid gland cells have both angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2) receptors, which the SARS-CoV-2 virus uses to enter cells. While SARS-CoV-2 has also been shown to precipitate other autoimmune diseases, there are only a few reported cases of new onset Graves' disease in the setting of SARS-CoV-2 infection. We report 2 patients who presented with severe thyrotoxicosis (thyroid storm and impending storm) that was likely precipitated by SARS-CoV-2 infection. Both patients had no previous history of hyperthyroidism, and potentially also developed Graves' disease after getting COVID-19. The addition of these cases to the medical literature will further highlight the fact that SARS-CoV-2 infection should be considered a causative agent for thyrotoxicosis when no other cause can be found, and that SARS-CoV-2 may be a potential trigger for autoimmune thyroid disease. It is important to know the SARS-CoV-2 status of such patients for infection control purposes, and to identify patients who may have their hospital course complicated by this disease. These cases may also help further our understanding of the etiology of autoimmune thyroid disease following a viral infection.